2020
DOI: 10.7759/cureus.11656
|View full text |Cite
|
Sign up to set email alerts
|

Trick or Treat? Licorice-Induced Hypokalemia: A Case Report

Abstract: The by-products of black licorice metabolism are toxic in high concentrations. Patients who consume large quantities of black licorice are at risk of developing an acquired syndrome of apparent mineralocorticoid excess. This presents clinically as hypertension, hypernatremia, and hypokalemia. Here, we present the unique case of a 74-year-old woman with a past medical history of neurogenic orthostatic hypotension, on fludrocortisone, who presented to the emergency department with asymptomatic hypokalemia (2.4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Licorice-induced AME is reversible, taking into account that the inhibitory action on 11-β-HSD type 2 lasts about two weeks. In addition, the renin-angiotensin-aldosterone system may take up to six months to recover to its previous level, which may be temporarily supplemented with potassium-saving diuretics, spironolactone, and dexamethasone, keeping in mind that glucocorticoids may be too strong and have more side effects [ 3 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Licorice-induced AME is reversible, taking into account that the inhibitory action on 11-β-HSD type 2 lasts about two weeks. In addition, the renin-angiotensin-aldosterone system may take up to six months to recover to its previous level, which may be temporarily supplemented with potassium-saving diuretics, spironolactone, and dexamethasone, keeping in mind that glucocorticoids may be too strong and have more side effects [ 3 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cases of hypokalemia and hypertension have been reported after daily ingestion of licorice tea or after short-term high dose [52][53][54]. In one case patient was combining licorice with the glucocorticoid medication fludrocortisone [55]. The active components of licorice, glycyrrhizinates, inhibit the enzyme responsible for inactivating cortisol and bind to mineralocorticoid receptors resulting in reversible hyper-mineralocorticoid effects [56].…”
Section: Licorice In Heart Diseasementioning
confidence: 99%
“…In any case, studies have clearly demonstrated adverse health effects after excessive licorice consumption (Deutch, Grimm, Wehland, Infanger, & Krüger, 2019), thus consumption as food should be limited to safe intake levels. Symptoms including hypertension, hypokalemia, and edema are well documented in review articles (Isbrucker & Burdock, 2006;Luís, Domingues, & Pereira, 2018;Nazari, Rameshrad, & Hosseinzadeh, 2017;Omar et al, 2012) as well as case reports including cardiac arrest (Albermann, Musshoff, Hagemeier, & Madea, 2010;Allcock & Cowdery, 2015;Benge, Shah, Yamaguchi, & Josef, 2020;Celik et al, 2012;Chehri, Holmager, Stender, & Friis-Hansen, 2021;Edelman, Butala, Avery, Lundquist, & Dighe, 2020;Kwon, Oh, & Choi, 2020;McHugh, Nagabathula, & Kyithar, 2021;Murphy, Agger, & Rainey, 2009;Støving et al, 2011;Varma & Ross, 2017). In Europe, these health concerns were addressed officially by the Scientific Committee on Food (SCF) who expressed the opinion that "regular ingestion should not exceed 100 mg glycyrrhizin per day from all sources, this figure is regarded as provisional until more extensive data becomes available" (SCF, 1992).…”
Section: Introductionmentioning
confidence: 99%